Electricity Reforms in Mali : A Macro-Micro Analysis of the Effects on Poverty and Distribution - Boccanfuso, Dorothee (2012)
This paper uses a computable general equilibrium (CGE) micro-simulation model to explore the distributional and poverty-related effects of price reform in the electricity sector of Mali, a poor country in West Africa. In the first part of the paper we analyse the distribution of electricity in Mali by income deciles, showing that few poor households are connected to the electricity grid. We then apply a sequential CGE micro-simulation model to track the transmission mechanisms between increases in electricity prices and changes in poverty and inequality among different household groups. Our results show that direct price increases have a minimal effect on poverty and inequality, whereas the general equilibrium effects of such increases are quite strong and negative. The compensating policies we tested do not help those who lose from the pricing reform. In fact they amplify the negative effects.